1989
DOI: 10.1002/polb.1989.090270711
|View full text |Cite
|
Sign up to set email alerts
|

Transport studies with model membrane

Abstract: The most recent theory for salt concentration dependence of biionic potential, developed by Ikeda and his colleagues on the basis of thermodynamics of irreversible processes, has been compared with that of Nozaki et al. to get a relationship for the calculation of theoretical values of biionic potential. The latter are in good agreement with the experimental data gathered for the parchment‐supported manganese ferricyanide membrane in contact with various alkali chloride solutions. The conclusion of selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…Study conducted in Ethiopia reported membrane potential increased with decrease in concentration (Damena et al, 2013) which was in line with the result of this study. There was also other study which supports this result (Saddiqi and Alvi, 1989). Variation of membrane conductance with increased drug concentration and temperature might be explained by taking the following points into consideration: The number of charged particles available for the transport of current; the extent of the sorption of permeants in the membrane phase; the variation of viscosity with concentration and temperature.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Study conducted in Ethiopia reported membrane potential increased with decrease in concentration (Damena et al, 2013) which was in line with the result of this study. There was also other study which supports this result (Saddiqi and Alvi, 1989). Variation of membrane conductance with increased drug concentration and temperature might be explained by taking the following points into consideration: The number of charged particles available for the transport of current; the extent of the sorption of permeants in the membrane phase; the variation of viscosity with concentration and temperature.…”
Section: Discussionsupporting
confidence: 83%
“…The other reason might be, when the hydrated ions approached to the pores of the membrane before effective interaction with phosphotidylcholine of the lipid, certain fraction of water molecules from the hydration shell of the ion and fixed sides might be removed. The negative entropy change of activation (-ΔS*) observed indicated that an ordered water molecules become less ordered in the most diluted solutions (Saddiqi and Alvi, 1989). Study conducted in India on ion transport studies through polystyrene based model membrane conductance data and absolute reaction rate theory reported activation energy decrease with increase in concentration and the value of change of entropy were negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand the amount of variation in the current was found to be depend on the many factors, such as applied potential, diffusion coefficient, initial concentration of components within membrane, the resting potential and the initial and final steady fluxes, in more complicated manner. 15 In order to estimate the flux at resting state, the following equation could be available; 16 (27) where C 0 α and C l α are bulk concentrations of ion α on the both sides of membrane and Pα is the membrane permeability to the ion α. Assuming that in the membrane, the potential gradient is a constant and the diffusion coefficient, Dα is a constant independent of concentration Pα may be reduced to (28) which, provided zαFV / 2RT, is small as compared with unity, is reduced to (29) where η α indicates excess free energy of the ion α. Inserting equation (29) into equation (27), we obtain the next equation (30) (30) Thus the fluxes at rest and the diffusion coefficients could be estimated from the data shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%